Elevated Plasma Marinobufagenin, An Endogenous Cardiotonic Steroid, Is Associated With Right Ventricular Dysfunction and Nitrative Stress in Heart Failure. (November 2015) - Kennedy, David J.; Shrestha, Kevin; Sheehey, Brendan; Li, Xinmin S.; Guggilam, Anuradha; Wu, Yuping; Finucan, Michael; Gabi, Alaa; Medert, Charles M.; Westfall, Kristen; Borowski, Allen; Fedorova, Olga; et al.
Abstract : Background—: Plasma levels of cardiotonic steroids are elevated in volume-expanded states, such as chronic kidney disease, but the role of these natriuretic hormones in subjects with heart failure (HF) is unclear. We sought to determine the prognostic role of the cardiotonic steroids marinobufagenin (MBG) in HF, particularly in relation to long-term outcomes. Methods and Results—: We first measured plasma MBG levels and performed comprehensive clinical, laboratory, and echocardiographic assessment in 245 patients with HF. All-cause mortality, cardiac transplantation, and HF hospitalization were tracked for 5 years. In our study cohort, median (interquartile range) MBG was 583 (383–812) pM. Higher MBG was associated with higher myeloperoxidase ( r =0.42, P <0.0001), B-type natriuretic peptide ( r =0.25, P =0.001), and asymmetrical dimethylarginine ( r =0.32, P <0.001). Elevated levels of MBG were associated with measures of worse right ventricular function (RV s ′, r =−0.39, P <0.0001) and predicted increased risk of adverse clinical outcomes (MBG≥574 pmol/L: hazard ratio 1.58 [1.10–2.31], P =0.014) even after adjustment for age, sex, diabetes mellitus, and ischemic pathogenesis. In mice, a left anterior descending coronary artery ligation model of HF lead to increases in MBG, whereas infusion of MBG into mice for 4 weeks lead to significant increases in myeloperoxidase, asymmetrical dimethylarginine, and cardiac fibrosis. Conclusions—: In the setting of HF, elevated plasma levels of MBG are associated with right ventricular dysfunction and predict worse long-term clinical outcomes in multivariable models adjusting for established clinical and biochemical risk factors. Infusion of MBG seems to directly contribute to increased nitrative stress and cardiac fibrosis. Abstract : Supplemental Digital Content is available in the text.